2007
DOI: 10.1084/jem.20062013
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferons protect neonates from acute inflammation through interleukin 10–producing B cells

Abstract: Newborns and infants are highly susceptible to viral and bacterial infections, but the underlying mechanism remains poorly understood. We show that neonatal B cells effectively control the production of proinflammatory cytokines by both neonatal plasmacytoid and conventional dendritic cells, in an interleukin (IL) 10–dependent manner, after Toll-like receptor (TLR) 9 triggering. This antiinflammatory property of neonatal B cells may extend to other TLR agonists (Pam3CSK4, lipopolysaccharide, and R848) and viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 55 publications
6
122
3
1
Order By: Relevance
“…It is noteworthy that, contrary to our findings, a recent study shows that the defective inflammatory response of neonatal mice due to increased IL-10 production by a B1 subset of B cells may increase their survival rate upon stimulation by various TLR agonists (18). The major difference between the studies is the use of D-GalN.…”
Section: 01) Data Are Presented As Mean Values (ϯSem) (D) Lethal contrasting
confidence: 53%
See 3 more Smart Citations
“…It is noteworthy that, contrary to our findings, a recent study shows that the defective inflammatory response of neonatal mice due to increased IL-10 production by a B1 subset of B cells may increase their survival rate upon stimulation by various TLR agonists (18). The major difference between the studies is the use of D-GalN.…”
Section: 01) Data Are Presented As Mean Values (ϯSem) (D) Lethal contrasting
confidence: 53%
“…In human, it has been reported that mononuclear cells from cord blood secrete lower amounts of TNF than those from healthy adults in response to TLR agonists (10)(11)(12)(13), whereas other studies draw opposite conclusions (14)(15)(16). Results from studies in mice also conflict because neonates produce either lower (17,18) or higher (19) levels of TNF compared with adults. The most consistent observation, however, is that the ratio of IL-6 to TNF is higher, whereas IFN-␥ is defective in neonates (10,11,20).…”
contrasting
confidence: 39%
See 2 more Smart Citations
“…These results showing no effect following elimination of the adaptive immune system are contrary to recently published data showing that CD5 ϩ B cells, a component of the neonatal adaptive immune system, are important in preventing lethal shock responses to CpG DNA in neonates through an anti-inflammatory pathway involving type I IFN and IL-10. 45 However, their model did not involve an infectious pathogen, whereas we used a model of severe polymicrobial sepsis with clinical relevance. Furthermore, since neonates exhibit an attenuated inflammatory response and increased sepsis mortality, 23 these cells may be contributing to the poor bacterial clearance and increased mortality induced by the infection.…”
Section: Discussionmentioning
confidence: 99%